MULTIVARIABLE CLOSED-LOOP IDENTIFICATION WITH CONSTRAINED MPC CONTROL: CASE-STUDY ON A C3/C4 SPLITTER - Sotomayor, Oscar A. Z. (2007)
This paper deals with the model re-identification in closed-loop systems with already existing MPC controllers. lt is assumed that the controller has a two-layer structure where the upper layer performs a simplified economic optimization in which the economic objective is represented as a linear combination of the process inputs. This is the case of several commercial MPC packages applied in industry. This work focuses on the case where the existing process model shows signs of deterioration and there is benefit in obtaining a new model. It is proposed a methodology where the test signal is introduced in the coefficients of the objective function of the economic layer. The approach allows the continuous operation of the system as the process constraints and product specification can be satisfied during the test. The application of the method is illustrated by simulation on a C3/C4 splitter of the oil industry. The method is simple to be implemented in existing commercial packages, and the results show that tne method has a good potential to be applied in practice.